Scalable AI-Powered Cyber Hygiene Models for Microenterprises and Small Businesses - Jeanette Uddoh; Daniel Ajiga; Babawale Patrick Okare; Tope David Aduloju (International Journal of Scientific Research in Civil Engineering, 2024)
Microenterprises and small businesses (MSBs) face escalating cyber threats, with 43% experiencing data breaches due to inadequate cyber hygiene practices. Limited resources, technical expertise, and scalable solutions exacerbate their vulnerability, hindering economic resilience in digital ecosystems. This paper proposes scalable AI-powered cyber hygiene models tailored for MSBs, leveraging machine learning, behavioral analytics, and automated tools to enhance security posture affordably. Through a mixed-method approach, including literature review, model development, and pilot testing with 50 MSBs across retail, healthcare, and services sectors, the study synthesizes insights from 120 peer-reviewed articles and industry reports from 2018 to 2024. The proposed models achieve 92% accuracy in detecting phishing and malware, reduce cyber incidents by 35%, and lower implementation costs by 40% compared to traditional solutions. Key findings highlight the models’ scalability, user-friendliness, and compliance with regulations like GDPR and CCPA, but challenges include limited digital literacy, integration with legacy systems, and cloud dependency. Opportunities involve integrating generative AI for real-time threat response and blockchain for auditability. The study contributes to cybersecurity literature by offering a practical, MSB-focused framework, bridging AI innovation with economic accessibility. For MSBs, the models provide cost-effective tools to mitigate risks, while policymakers gain insights to support digital inclusion. Future research directions include AI explainability, zero-trust integration, and models for underserved regions. By addressing these issues, this paper underscores the transformative potential of AI-powered cyber hygiene in empowering MSBs, fostering secure, resilient, and inclusive digital economies.